Ecophysiologie de la maturation sexuelle et de la ponte de l'huître creuse Crassostrea gigas : réponses métaboliques (respiration) et alimentaires (filtration, absorption) en fonction des différents stades de maturation - Soletchnik, Patrick; Razet, Daniel; Geairon, Philippe; Faury, Nicole; Goulletquer, Philippe (Gauthier-villars, 1997)
The study of maturation and spawning of the oyster is part of a research program to investigate the summer mortalities of the oysters, Crassostrea gigas in Marennes-Oléron Bay. Four maturity stages were simultaneously obtained by diet and thermal conditioning (immature, low maturation, mature and post-spawning stages). Measurements of clearance, filtration, absorption and respiration rates allowed a calculation of the scope for growth and hence an estimation of the oyster's energetic budget at various maturity stages. Male and female oysters had similar physiological responses. The filtration rate ranged from 2.4 to 2.6 1.h(-1) at the early stages of maturation and decreased to 1.8 1.h.' during the maturity stage. Growth rate resulting from gonad development did not induce filtration rate changes. Mature 2.5 and 1.5-year-old oysters showed a negative energy budget reaching -15 and -90 J.h(-1) respectively. By contrast, non-ripe oysters had scope for growth in the range 110 to 170 J.h(-1). A negative energy budget during the high maturation stage resulted from a reduced absorption efficiency. A new allometric relationship for the respiration model of C. gigas was defined during vitellogenesis with a 0.574 coefficient value. Based on Our results, the oyster's physiological weakness during vitellogenesis should be considered as a part of explanation for spring and summer mortalities of cultured oysters in Marennes-Oléron Bay. L'étude de la maturation et de la ponte de l'huître creuse Crassostrea gigas, s'intègre dans une large problématique visant à comprendre les causes de mortalité qui surviennent épisodiquement dans le bassin de Marennes-Oléron au printemps et en été. Un conditionnement thermique et alimentaire des élevages permet d'obtenir simultanément des huîtres à tous les stades de maturité sexuelle. Le calcul des taux de filtration, consommation, absorption et respiration permet d'estimer le potentiel de croissance, et donne le bilan énergétique des huîtres aux différents stades sexuels. Les réponses ...